2017
DOI: 10.1097/mjt.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Inferiority Study: Modified Dual Therapy Consisting Higher Doses of Rabeprazole Is as Successful as Standard Quadruple Therapy in Eradication of Helicobacter pylori

Abstract: The aim is to compare high-dose rabeprazole and amoxicillin containing modified dual therapy (MDT) with bismuth subcitrate containing standard quadruple therapy (SQT) as the first-line Helicobacter pylori eradication treatment in terms of efficacy, safety, and adherence to treatment. A total of 200 consecutive patients diagnosed endoscopically with nonulcer dyspepsia with H. pylori infection were randomly assigned into 2 groups, 1 treated with amoxicillin 750 mg thrice daily plus rabeprazole 20 mg thrice daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 27 publications
0
53
0
3
Order By: Relevance
“… 26 40 The characteristics of the included trials are shown in Table 1 . Of the 15 trials, 11 were conducted in Asia, 29 33 , 35 40 3 in Europe, 27 , 28 , 34 and 1 in North America. 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 26 40 The characteristics of the included trials are shown in Table 1 . Of the 15 trials, 11 were conducted in Asia, 29 33 , 35 40 3 in Europe, 27 , 28 , 34 and 1 in North America. 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 trials, 11 were conducted in Asia, 29 33 , 35 40 3 in Europe, 27 , 28 , 34 and 1 in North America. 26 HDDT was given three times daily in four trials, 26 , 28 , 30 , 34 and four times daily in the others. 27 , 29 , 31 33 , 35 40 Six trials used TT, 26 , 28 31 , 36 seven used BQT, 27 , 33 35 , 37 , 38 , 40 one used non-BQT, 39 and one used both TT and ST as control regimen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations